Acquisition of Nonadjacent Phonological Dependencies in the Native Language During the First Year of Life - Gonzalez-Gomez, Nayeli; Nazzi, Thierry (Infancy, 2012)
Languages instantiate many different kinds of dependencies, some holding between adjacent elements and others holding between nonadjacent elements. In the domain of phonology–phonotactics, sensitivity to adjacent dependencies has been found to appear between 6 and 10 months. However, no study has directly established the emergence of sensitivity to nonadjacent phonological dependencies in the native language. The present study focuses on the emergence of a perceptual Labial‐Coronal (LC) bias, a dependency involving two nonadjacent consonants. First, Experiment 1 shows that a preference for monosyllabic consonant‐vowel‐consonant LC words over CL (Coronal‐Labial) words emerges between 7 and 10 months in French‐learning infants. Second, two experiments, presenting only the first or last two phonemes of the original stimuli, establish that the LC bias at 10 months cannot be explained by adjacent dependencies or by a preference for more frequent coronal consonants (Experiment 2a & b). At 7 months, by contrast, infants appear to react to the higher frequency of coronal consonants (Experiment 3a & b). The present study thus demonstrates that infants become sensitive to nonadjacent phonological dependencies between 7 and 10 months. It further establishes a change between these two ages from sensitivity to local properties to nonadjacent dependencies in the phonological domain.